2018–2019 Florida Citrus Production Guide: Decay Control of Florida Fresh Citrus - Mark A. Ritenour; Jiuxu Zhang; Liliana M. Cano; Megan M. Dewdney (EDIS)
Citrus fruit decay is one of the most important constraints that affect fresh citrus quality and marketing values. It is most often caused by fungal or oomycete pathogens that grow and develop in the hot and wet conditions typical of Florida. This 5-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Mark A. Ritenour, Jiuxu Zhang, Liliana M. Cano, and Megan M. Dewdney, and published by the Horticultural Sciences Department, January 2019.